2009 European Control Conference (ECC) 2009
DOI: 10.23919/ecc.2009.7075134
|View full text |Cite
|
Sign up to set email alerts
|

Supervisory control synthesis for a patient support system

Abstract: The increasing complexity of systems and the increasing market pressure necessitate the need for methods to maximize reuse and to minimize the effort to develop new systems. Modelbased engineering is one of these methods. It uses models and model-based techniques in the development process to analyze and synthesize systems and components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 12 publications
(1 reference statement)
0
24
0
Order By: Relevance
“…Although several applications reported in the literature, e.g., [15,22,23], include implementation of synthesized supervisors on a PC or a PLC, they are usually put in practice in an academic setup. To our knowledge, the industrial applications described in [12,18,34] are ones of the few that actually refer to an existing industrial product. Recently, a project is started in the automotive application area, where supervisor synthesis techniques are used in the design of the discrete part of a cruise control system.…”
Section: Industrial Casesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several applications reported in the literature, e.g., [15,22,23], include implementation of synthesized supervisors on a PC or a PLC, they are usually put in practice in an academic setup. To our knowledge, the industrial applications described in [12,18,34] are ones of the few that actually refer to an existing industrial product. Recently, a project is started in the automotive application area, where supervisor synthesis techniques are used in the design of the discrete part of a cruise control system.…”
Section: Industrial Casesmentioning
confidence: 99%
“…In [34], supervisor synthesis is applied to a support system used to position patients in an MRI scanner of Philips Healthcare (http://www.medical.philips.com). MRI stands for magnetic resonance imaging, which is a medical imaging technique used in radiology to visualize detailed internal structures.…”
Section: Mri Scannermentioning
confidence: 99%
“…1 has been successfully applied in several industrial case studies involving movement control of a patient support system for a Philips MRI scanner [29], coordination of a printing process of an Océ High-tech printer [30], and movement coordination of Theme park vehicles [31]. In all cases, the synthesized supervisory controllers were successfully tested using hardware-in-the-loop integration, where the hardware was supervised by employing the model of the supervisory controller for which we used appropriate interfaces with the machines that employ the controller protocols [12].…”
Section: Industrial Applicationmentioning
confidence: 99%
“…The goal of the case study MRI scanner reported in [29] is safe positioning of patients inside an MRI scanner. To this end, models of the patient support system and the user interface of the machine have been made, leading to 6.3 · 10 9…”
Section: Industrial Applicationmentioning
confidence: 99%
“…In this way, the specification of the control logic is less vulnerable for changes in the physical system. An example of such work is the work on supervisory control synthesis by Rooda et al, e.g., in [83,100].…”
Section: Separating Design Rationale From Control Logicmentioning
confidence: 99%